The Impact of Local Government Accounting Systems and Performance-Based Budgeting on Local Government Performance Accountability - Marwah Yusuf (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2020)
The main objective of this research is to study and understand the impact of the Government Accounting System and performance-based budgeting carried out in Makassar Regional Department OPD. This research applies a quantitative approach to all the city's employees, who are all participants in the Makassar Government financial department's SIPK application. These were 75 respondents from 25 offices selected through the purposeful sampling technique. Data were obtained through the distribution of questionnaires, and documentation. The data was tested using experimentally derived, statistical techniques that explore homoscedasticity, heteroscedasticity, and non-hypothesis (partial test, simultaneous test, and the coefficient of determination). We learned that the Local Governmental Accountability System has a positive and significant effect on the government's performance; likewise, the findings showed that Performance-Based Budgeting improves government performance and government accountability.